Answer:
The solutions are [tex]x=\frac{1+\sqrt{7}}{2}[/tex] and [tex]x=\frac{1-\sqrt{7}}{2}[/tex]
Step-by-step explanation:
we have
[tex]0=-2x^{2}+2x+3[/tex]
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]-3=-2x^{2}+2x[/tex]
Factor the leading coefficient
[tex]-3=-2(x^{2}-x)[/tex]
Complete the square. Remember to balance the equation by adding the same constants to each side.
[tex]-3-0.5=-2(x^{2}-x+0.5^{2})[/tex]
[tex]-3.5=-2(x^{2}-x+0.5^{2})[/tex]
Rewrite as perfect squares
[tex]-3.5=-2(x-0.5)^{2}[/tex]
[tex]7/4=(x-0.5)^{2}[/tex]
square root both sides
[tex]x-0.5=(+/-)\sqrt{\frac{7}{4}}[/tex]
[tex]x-\frac{1}{2}=(+/-)\frac{\sqrt{7}}{2}[/tex]
[tex]x=\frac{1}{2}(+/-)\frac{\sqrt{7}}{2}[/tex]
[tex]x=\frac{1+\sqrt{7}}{2}[/tex]
[tex]x=\frac{1-\sqrt{7}}{2}[/tex]